1997
DOI: 10.1046/j.1365-3083.1997.d01-87.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Affects the Seasonal Increase in Specific IgE and Interleukin‐4 in Serum of Patients with Seasonal Allergic Rhinitis

Abstract: This study was designed to determine seasonal changes in cytokines, soluble CD23 and specific IgE in the serum of patients with seasonal allergic rhinitis, and the effect of immunotherapy on these seasonal changes. Fifty-four patients with seasonal allergic rhinitis caused by Japanese cedar pollens were divided into a medication group and an immunotherapy group. The patients of the medication group were treated with nonsedating antihistamines alone during the pollen season. The patients of the immunotherapy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
33
1
1
Order By: Relevance
“…It has been reported that subcutaneous injection of conventional Japanese cedar pollen allergen reduced specific IgE and Th2 responses after more than 3 years of treatment [24]. PEG-fusion reduced specific IgE after four injections in mice and monkeys, and specific Th2 responses in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that subcutaneous injection of conventional Japanese cedar pollen allergen reduced specific IgE and Th2 responses after more than 3 years of treatment [24]. PEG-fusion reduced specific IgE after four injections in mice and monkeys, and specific Th2 responses in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The details and justification of the methods used in this study have been described elsewhere. 11,12 In brief, microtitration plates were coated with anti-IL-5 monoclonal antibody (MoAb) (JES1-39D10), 2 µg/ mL, and anti-IFN-␥ MoAb (ANOC 1611), 10 µg/mL, or anti-TNF-␣ MoAb (ANOC 706), 2 µg/mL, in 100 µL per well of PBS, pH 7.4. Following overnight incubation at 4°C, the wells were blocked with 1% skim milk in PBS solution for at least 1 hour at room temperature and washed 3 times with PBS containing 0.05% polysorbate 20 (washing was always performed with this buffer).…”
Section: Determination Of Total Ige Il-5 Ifn-␥ and Tnf-␣ In Culturmentioning
confidence: 99%
“…Interleukin-4 was measured with a chemiluminescent ELISA, and the justification of the method employed in this study has been described elsewhere [10,17]. In brief, microtitre plates were coated with mouse monoclonal anti-human IL-4 antibody (R & D Systems, Minneapolis, MN, USA) and after incubation with serum samples or purified recombinant IL-4 (R & D Systems) plates were developed with biotinylated mouse anti-human IL-4 antibody (Pharmingen, San Diego, CA, USA) followed by avidine-alkaline phosphatase conjugate (Tago, Camarillo, CA, USA).…”
Section: Patientsmentioning
confidence: 99%
“…Thus, IL-4 may be the most important cytokine involved in the allergic pathogenesis, although other cytokines derived from Th2-like cells are likely to take some part in mediating allergic disorders [34,35]. Several studies have documented a significant elevation of serum IL-4 in atopic individuals compared with nonatopic controls [17,30,36]. We previously demonstrated that serum levels of IL-4 were elevated in perennial allergic rhinitis and the elevation was down-regulated by prolonged immunotherapy [17].…”
Section: Serology Of Perennial Rhinitis During Immunotherapy 175mentioning
confidence: 99%
See 1 more Smart Citation